Evaluation of antioxidant activity of Eucheuma spinosum and Sargassum crassifolium through 1, 1 - DIPHENYL - 2-PICRYLHYDRAZYL (DPPH) method and phytochemical screening. - Calizo, Czarmina Donna Padullon (2012.)
The study aims to evaluate the antioxidant activity of E. spinosum and S. crassifolium that are potential natural sources of antioxidants. The cleaned E. spinosum (637.53 g) and S. crassifolium (288.46 g) samples were macerated for 48 hours using 80 percent methanol. The crude methanol, n - hexane and DCM extracts of these two seaweed samples were assayed for their free radical scavenging activities using the DPPH Free Radical Scavenging Method Ascorbic acid (250 mg/L) and DPPH (20 mg/L) solutions were used as positive and negative controls respectively. The results showed that all three extracts of E. spinosum had low free radical scavenging activities, while all three (crude methanol, n-hexane and DCM) extracts of S. crassifolium significant antioxidant activities (50.93 percent, 61.07 percent and 57.89 percent respectively). since the n-hexane extract of s. crassifolium showed the highest antioxidant activity from the samples, its half maximal effective concentration was measured and found to be 76.69 mg/L and was higher than Ascorbic Acid (12.42 mg/L). In contrast to the very low free radical scavenging activity of E. spinosum, it contained several phytochemicals whereas only terpenes were present in s. crassifolium.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Eucheuma spinosum; Sargassum crassifolium